2015
DOI: 10.1017/s1368980015000865
|View full text |Cite
|
Sign up to set email alerts
|

Intakes of apple juice, fruit drinks and soda are associated with prevalent asthma in US children aged 2–9 years

Abstract: Objective: High soft drink consumption has been linked with asthma. Anecdotal evidence links high-fructose corn syrup with asthma. The receptor of advanced glycation end products (RAGE) has emerged as a mediator of asthma. The objectives of the present study were to: (i) assess the correlation between intake of beverages containing excess free fructose (EFF beverages) and asthma in children; and (ii) epidemiologically test the mechanistic hypothesis that intake of high EFF beverages, such as apple juice or bev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(112 citation statements)
references
References 34 publications
8
96
4
1
Order By: Relevance
“…There was no association with orange juice [26]. It is possible that enFruAGE contribute to inflammation beginning in childhood, as inflammation is commonly observed in children with asthma [9], including mild and moderate asthma [78].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…There was no association with orange juice [26]. It is possible that enFruAGE contribute to inflammation beginning in childhood, as inflammation is commonly observed in children with asthma [9], including mild and moderate asthma [78].…”
Section: Discussionmentioning
confidence: 91%
“…It has been hypothesized that the association between SSB and prevalence of these chronic comorbid diseases may be due to underlying fructose malabsorption, which results after consumption of foods with a high fructose to glucose ratio (unpaired excess free fructose) -as occurs in high fructose corn syrup -but not after consumption of sucrose. Consumption of high fructose to glucose ratios results in elevated amounts of unabsorbed fructose in the gut that may contribute to the intestinal in situ formation of AGE [23][24][25][26][27]. Importantly, emerging science provides evidence that there may be a metabolic connection of unknown etiology with each of these comorbid conditions (asthma [28], chronic bronchitis [24], autoimmune arthritis [25], T2D [29], and CHD [30]), and that each should be redefined as a multi-system disorder involving the gut.…”
Section: Introductionmentioning
confidence: 99%
“…Recent cross-sectional studies from DeChristopher and colleagues indicated that the consumption of HFCS or fructose sweetened beverages is associated to asthma and bronchitis in adults and to asthma in children [96][97][98]. Authors suggest an interesting mechanistic hypothesis, according to the in vitro observations of Bains and Gugliucci [99], of an intestinal formation of AGEs from excess free fructose intake which may be absorbed in the circulation and induce a systemic inflammatory condition through the binding to RAGE, thus contributing to lung diseases and impaired immune response.…”
Section: Dietary Sugar-induced Glycation and Pathogenic Role In Diseasesmentioning
confidence: 99%
“…13 High fruit juice consumption has been associated with an increased risk of asthma in children 8. This association may be due to high excess fructose fruit juices such as apple, rather than other juices low in excess fructose such as orange, which may be protective 9. A possible mechanism for the variation in these findings is that consumption of fruits high in excess free fructose leads to the formation of proinflammatory advanced glycation end products (AGE) in the intestine, which are absorbed into the circulation, causing a systemic immune response.…”
Section: Introductionmentioning
confidence: 99%